A new species of eriophyoid mite (Acari: Eriophyoidea: Eriophyidae) on Leucadendron argenteum (L.) R. Br. from South Africa - Pye, Daniel R. L. (Zootaxa, 2011)
A new vagrant eriophyoid mite species, collected from plant material imported into the United Kingdom, is described and illustrated: Aceria argentae n. sp. found on Leucadendron argenteum (L.) R. Br. (Proteaceae) from South Africa. A review of the eriophyoid mite species known from plants in the Proteaceae is also provided and recent findings of non-native eriophyoid mites in the United Kingdom are discussed.